Article RETRACTED due to manipulation by the authors Reducing Dysmenorrhea In School-Aged Teenagers By Practising Yoga: A Literature Review - Jihan Faira Zanada; Hendra Setyawan; Nugroho Susanto; Ridho Bahtra; Tiok Wijanarko; Khoiril Anam; Gema Fitriady; José Vicente García-Jiménez; Ratko Pavlovic; Agnieszka Magdalena Nowak (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Dysmenorrhea is the term used to describe lower abdominal pain that women feel during their menstrual cycle. Teens suffering from menstrual pain typically have lower abdominal cramps and other symptoms that interfere with day-to-day activities. An alternative to medication for treating menstruation discomfort is yoga. This study aimed to ascertain whether yoga may lessen dysmenorrhea in teenagers enrolled in school. This approach uses the MEDLINE/PubMed, Scopus, and Google Scholar databases to review literature. The PRISMA approach utilized for this literature review was adhered to during the article selection process. The research's selection criteria comprised works published within the last five years, specifically from 2018 to 2023. Yoga was employed to lessen dysmenorrhea discomfort in the research population, consisting of young women with monthly pain. Between 2018 and 2023, 666 studies were discovered to have satisfied the publication selection requirements. Fifteen journals that fit the requirements for this study were identified through the PRISMA route search. According to the data, yoga has been shown to have a calming effect on teenage menstrual discomfort in 15 journals. Thus, yoga is a successful non-pharmacological management strategy for lowering dysmenorrhea in school-age teenagers. This is because yoga may be calming, encouraging the body to release endorphins, which function as organic painkillers. Yoga is a mild activity that helps the body avoid stiffness, pressure, pain, and tiredness while increasing flexibility safely. It enhances lung capacity when breathing, improves blood circulation, eases physical and emotional stress, and lessens pain. Additionally, practising yoga helps women with PMS feel more at ease by reducing dangerous inflammatory secretions.